'I am the master of my fate': digital technology paradoxes and the coping strategies of older consumers. Issue 3 (12th February 2022) - Wilson-Nash, Carolyn; Tinson, Julie
ABSTRACT: The UK Government and charity-based initiatives encourage the use of digital devices to improve connectivity and address health care challenges across an escalating, ageing population. However, research on the lived experiences of older adults using technology is limited. The aim of this study is to build on technology paradox theory to provide a greater understanding of older adults' use of digital devices and the associated coping strategies that are adopted. A qualitative approach, employing event-based diaries, reveals functional, social and psychological paradoxes as well as influences on self-worth. The findings also identify how older adults adapt to the challenges of such technology paradoxes by developing novel coping strategies such as, adjusting and acceptance. Furthermore, implications for policy and practice are established.